In-vitro activation of complement system by lactic acidosis in newborn and adults - Friederike Hecke; Thomas Hoehn; Evelyn Strauss; Michael Obladen; Josef Sonntag (Hindawi Limited, 2001)
Introduction: Complement activation occurs secondary to a variety of external stimuli. Lactic acidosis has been previously shown to activate the complement factors C3a and C5a. In the present investigation we examined the differential effect of lactic acidosis on anaphylatoxin levels in cord and adult blood. Furthermore we aimed to determine if the entire complement cascade could be activated by lactic acidosis.